RULES AND ETHICS OF MEMORISING THE GLORIUS QUR’AN: A STUDY FROM AL-FARA’ID AL-JALILAH OF SHAYKH ABDULLAH BN FODUYE - Muhammad, Bala Abubakar (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2024)
Memorization of the Qur'an was one of the important areas that Muslims in the past have really worked on, in order to preserve it from distortion, this was in line with the promise of Allah the Most High for its protection as Q.15:9 says: “Verily, it's We who revealed the Dhikr (i.e. the Qur'an) and surely We will guard and protect it.” As-Sa'ady said: the protection is during and after revelation. The paper Intend to highlights on rules and ethics of memorization of the Glorious Qur’an as pointed out by Shaykh Abdullah bn Foduve in his book al-Fara’id al-Jalilah wasaid al-Fawaid al-Jamilah fi Ulum al-Qur’an. In the review authors made an effort to show the importance, rules and ethics for Qur’anic memorization in the content of the book under study, it discusses on the supportive majors on memorization of the glorious Qur'an. The paper also recommends to the Qur'anic Schools, Islamiyya, Tsangaya and individual to follow the teachings of the book.